Soluble Covalent Organic Polymer for the Flexible Electrode of Supercapacitors - Mi, Chunxia; Peng, Peng; Xiang, Zhonghua (Frontiers in Materials, 2019)
Covalent organic frameworks (COFs) have emerged promising potentials for the fabrication of flexible supercapacitors. Numerous efforts are devoting to the promotion of processability of COFs and broaden their applications in practical devices. Herein we have developed a fully conjugated two-dimensional manganese based COF material (termed as COFBTC-Mn) with nitrogen coordinated metal centers. The unique structures of COFBTC-Mn endow it with high solubility via an in-situ exfoliation pathway and the capability to adsorb onto carbon-based matrix by electrostatic force. COFBTC-Mn demonstrated superior processability, reliability and repeatability for the fabrication of flexible electrodes of supercapacitors. Besides, superior to the electrodes based on traditional insoluble COFs, our as-prepared flexible electrodes exhibited a specific capacitance as high as 325 F g-1 with the current density of 0.2 A g-1 and excellent stability after charge/discharge cycles.